Supplementation of high nitrogen agaricus compost: Yield and mushroom quality - Pardo-Gimenez, A.; Pardo-González, J. E.; Cunha Zied, D. [UNESP] (My University, 2017)
Supplementation to increase the quality and yield of white button mushrooms (Agaricus bisporus) consists of the addition of nutrients, particularly proteins, to the compost. In this study, the effect of mushroom cultivation on applying a delayed-release nutrient supplement to Phase II composts was evaluated. Two application dosages and composts with high nitrogen contents were used. Depending on the compost and supplement dosage used, increases in biological efficiency ranging between 6.2 and 22.3% were obtained. An excellent response to supplementation can be obtained even when using composts with high nitrogen contents (in our case, 2.45 and 2.61% sms) during spawning. It is additionally conceivable that the application of supplements to composts with lower N contents or the application to spawned compost would provide an even better yield, without adversely affecting the quality of the harvested mushrooms. This practice is of considerable interest because of the economic benefit.
Keywords: Agaricus bisporus; Business category; C/N ratio; Mushroom technology; Yield